m6A: a novel strategy for osteoporosis treatment - Yan, Chunlu; Xiao, Xiaolong; Yang, Fan; Shi, Yangyang; Wan, Qiao; Zhang, Yan; An, Fangyu (Frontiers in Cell and Developmental Biology, 2025)
Osteoporosis (OP) is a systemic metabolic disease characterised by increased bone fragility, with bone loss being the primary cause of its onset and progression. Regulating the dynamic balance between osteoblast (OB) formation and osteoclast-mediated bone resorption is crucial for preventing bone loss in OP. N6-methyladenosine (m6A), the most abundant and common RNA modification, is regulated by various proteins, including m6A methyltransferases, demethylases, and binding proteins. m6A methylation plays a key role in bone metabolism in OP, influencing the osteogenic and adipogenic differentiation of mesenchymal stem cells (MSCs), the osteogenic differentiation and bone formation capacity of OBs, as well as osteoclastic differentiation and resorptive activity. However, the specific molecular mechanisms through which m6A methylation regulates bone metabolism in OP remain incompletely understood. In this review, we comprehensively discuss the structure and function of m6A and summarise the roles of m6A methyltransferases, demethylases, and binding proteins. We also examine the regulatory mechanisms of m6A in MSCs, OBs, and osteoclasts, and discuss associated targeted therapies. This overview of the research on m6A is expected to highlight valuable insights and the translational potential for developing treatment strategies for OP.